Investigation of the pharmacological, behavioral, and biochemical effects of boron in parkinson-indicated rats: Effects of Boron on Rotenone-Induced Parkinson’s Disease - Ozdemir, Hulya Sagmanligil; Yunusoglu, Oruç; Sagmanligil, Vedat; Yasar, Semih; Colcimen, Nese; Goceroglu, RezzanTemelli; Catalkaya, Ege (Cellular and Molecular Biology, 2022)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder of the central nervous system. In different studies, it has been investigated that boric acid has positive effects on different mechanisms that are important in PD. The aim of our study was to investigate the pharmacological, behavioral and biochemical effects of boric acid on rats with experimental PD with Rotenone. For this purpose, Wistar-albino rats were divided into 6 groups. Only normal saline was applied subcutaneously (s.c) to the first control and sunflower oil to the second control group. Rotenone was administered (s.c) to 4 groups (groups 3-6) at a dose of 2 mg/kg for 21 days. Only rotenone (2mg/kg, s.c) was administered to the third group. Boric acid was administered intraperitoneally (i.p.) at 5 mg/kg, 10 mg/kg, and 20 mg/kg to groups 4, 5, and 6, respectively. During the study, behavioral tests were applied to the rats, and then histopathological and biochemical analyzes were performed from the sacrificed tissues. According to the data obtained, a statistically significant difference (p<0.05) was observed between the Parkinson’s group and the other groups in motor behavior tests, excluding the catalepsy test. Boric acid exhibited dose-dependent antioxidant activity. As a result of the histopathological and immunohistochemical (IHC) examination, a decrease in neuronal degeneration was observed at the increasing doses of boric acid, while gliosis and focal encephalomalacia were rarely encountered. There was a significant increase in tyrosine hydroxylase (TH) immunoreactivity, especially in group 6, with a dose of 20 mg/kg of boric acid. From these results, we conclude that the dose-dependent effect of boric acid may protect the dopaminergic system with antioxidant activity in the pathogenesis of PD. However, the effectiveness of boric acid on PD needs further investigation in a larger, more detailed study using different methods.